Enriquecimento Semântico de Serviços para Provimento de Dados Conectados em SOA - Oliveira, Bruno C. N.; Huf, Alexis; Salvadori, Ivan; Siqueira, Frank (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
One of the main challenges concerning information systems that deal with heterogeneous services and data consists in achieving semantic interoperability. Several approaches have been proposed to assist in the semantic enrichment of services, by using domain ontologies. Nevertheless, most of the proposals found in the literature focus on the enrichment of the service description, neglecting data representations provided by such services. This work presents an approach to dynamically provide representations in the form of linked data in a service-oriented system. Therefore, we propose an architecture to build/evolve ontologies and to enrich services with concepts defined by such ontologies. As a way to increase the semantic expressiveness of services, the architecture employs ontology matching techniques to explore equivalences in external sources. The results show that the proposed solution can achieve satisfactory precision and coverage levels, as well as better performance compared to other approaches.